Pembelajaran Sastra Berbasis Kearifan Lokal pada Siswa Kelas VIII-1 SMP YP. Pangeran Antasari Medan - Bakara, Pestaria; Tambunan, Laura Yohanna; Panggabean, Putri Yola Yolanda; Cibro, Lenny; Sinaga, Relika; Akbar, Syahrizal (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2019)
The purpose of this study was to find out the effective steps in literary learning based on local wisdom and to find out the process of literary learning based on local wisdom in class VIII-1 of SMP YP. Pangeran Antasari Medan Academic Year 2018/2019. The approach used in this study is a qualitative approach. The results of this study only describe or construct in-depth interviews with the subject of research so that it can provide a clear picture of the understanding of local wisdom-based literary learning in class VIII-1 of SMP YP. Pangeran Antasari Medan. This study does not use populations and samples, but uses research subjects. In this study, the data sources were obtained from the determined research sites, namely in class VIII-1 of SMP YP. Antasari Medan. The collection technique in this study consisted of three ways, namely Observation, Interview or interview, and Questionnaire. The results of the study indicate that the learning process and short story learning steps are based on local wisdom in class VIII-1 of SMP YP. Pangeran Antasari Medan is good.Keywords: literary learning; short stories; and local wisdom.